2016
DOI: 10.2340/16501977-2046
|View full text |Cite
|
Sign up to set email alerts
|

Postural Assessment Scale for Stroke Patients Scores as a predictor of stroke patient ambulation at discharge from the rehabilitation ward

Abstract: Objective: The Postural Assessment Scale for Stroke Patients (PASS) is used to assess static and dynamic balance of stroke patients. PASS has demonstrated good measurement pro perties for reliability and validity, but its predictive effect for ambulation in stroke patients has not been investigated. The aim of this study was to investigate the predictive value of PASS for ambulation in patients with stroke after inpa tient rehabilitation. Methods: In this retrospective study, a total of 341 stroke pa tients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 29 publications
3
16
0
2
Order By: Relevance
“…Walking velocity as measured by SSGS on admission was identified as a potential predictor of community ambulation at discharge. The result of the study supports the findings from previous studies indicating that balance and walking velocity outcome measures on admission may predict the walking capacity of patients with stroke at discharge 6,8,27–31. The results of this study support findings from others that also analyzed the use of the BBS in predicting household and community ambulators at discharge 8,13.…”
Section: Discussionsupporting
confidence: 89%
“…Walking velocity as measured by SSGS on admission was identified as a potential predictor of community ambulation at discharge. The result of the study supports the findings from previous studies indicating that balance and walking velocity outcome measures on admission may predict the walking capacity of patients with stroke at discharge 6,8,27–31. The results of this study support findings from others that also analyzed the use of the BBS in predicting household and community ambulators at discharge 8,13.…”
Section: Discussionsupporting
confidence: 89%
“…In clinical practice, various clinical tools have been used to assess dynamic balance and walking performance in stroke patients such as functional independent measure (10), functional classi cation ambulation (11) and timed walking tests (12) but these clinical measures provide limited information to plan treatment and outcome measurements. In addition, it has been reported that dynamic balance of chronic stroke patients during walking cannot be measured with static balance scales (13).…”
Section: Introductionmentioning
confidence: 99%
“…PASS is a practical test that is easy to apply and understand to assess postural control and balance in patients with low physical performance levels. They also showed that it could be used in determining the discharge recommendations in acute care (14) and in predicting ambulation levels (15). An and Lee ( 16) examined the validity and reliability of PASS in patients with chronic stroke, and found the intra-rater (ICC 3,1=0.97, 95% CI) and absolute (SEM=1.01) reliability, and BBS to be high.…”
Section: Discussionmentioning
confidence: 99%